Al-Qāḍī ‘Abd Al-Jabbār’s View on Khalq Al-Qur’ān: Study of the Book Al-Mugnī fī Abwāb Al-Tawḥīd wa Al-‘Adl - Ibnu Rusdi (Universitas Islam Negeri Mataram, 2015)
In the Islamic doctrine, the Qur’an is divine and sacred. Although majority Muslims believe that the Qur’an is revealed divine words, they dispute over the sacredness of the Qur’an. One emerging central question is whether the Qur’an is created (jadīd) or not (qadīm). One Muslim sect that considers the Qur’an as creature is Mu’tazila, that used to be adopted as the state theological school during the Abbasid period, especially under al-Ma’mūn. This articles discusses the notion of khalq al-Qur’ān (the creatdeness of the Qur’an) advanced by Mu‘tazila scholar al-Qāḍi ‘Abd al-Jabbār in his work al-Mugnī fī Abwāb al-Tawḥīd Wa al-‘Adl. In general, al-Jabbār’s view reflects his school’s view on the Qur’an. When advancing his opinion that the Qur’an is created, he means to purify the concept of Oneness (tawḥīd) of God. Because al-Jabbār perceives only God is qadīm, and He is the only uncreated, other than Him must be created, including the Qur’an since it consists of letters and consonants. DOI: http://dx.doi.org/10.20414/ujis.v19i2.347